Impacts of Trade Liberalization on the New York Horticultural Sector - Gerald B. White; Nelson L. Bills; Isabel Schluep (Cornell University, Charles H. Dyson School of Applied Economics and Management, 2002)
Growers of horticultural products in New York State have become increasingly concerned about their position in the global marketplace and the effects of trade policy on the economic vibrancy of their businesses. Although competitive issues with Canadian producers of like commodities have drawn attention in New York State for many years, the interest has become more intense in the last two decades. Trade liberalization on a worldwide scale in recent decades has offered opportunities, but challenges as well, for a number of commodities produced on New York farms. The purpose of this report is to discuss these matters in a systematic way.
Keywords: 330; Außenhandelsliberalisierung; Gartenbau; Landwirtschaft; New York <Staat>